A method for preparing a fluorine-containing functional group adsorbent modified with cellulose as a carrier

By post-modifying the fluorine-containing functional groups on cellulose, an efficient adsorbent material was prepared, which solved the problems of poor selectivity, low adsorption amount and high cost in lithium ion adsorption, and achieved the lithium ion recovery effect with high selectivity and high adsorption capacity.

CN116173915BActive Publication Date: 2025-03-28ANHUI AGRICULTURAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310222615.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-09
Publication Date
2025-03-28
Estimated Expiration
2043-03-09

AI Technical Summary

Technical Problem

The existing adsorbents have poor selectivity, low adsorption amount and high cost in lithium ion adsorption, making it difficult to effectively recover lithium ions in lithium-containing wastewater.

Method used

Using cellulose as a support, after postmodification of fluorine-containing functional groups, an adsorbent material is prepared to modify pentafluoropropionate groups with cellulose as a support. The method includes drying the mixture of cellulose and ionic liquid in a vacuum drying oven, then magnetically stirring in an oil bath pot until the cellulose is completely dissolved, followed by modification reactions of iodine element and pentafluoropropionic anhydride, and finally obtaining the adsorbent material through multiple cleaning and drying.

Benefits of technology

This adsorbent material exhibits high selectivity and adsorption capacity in terms of adsorption properties of lithium ions, with a maximum adsorption capacity of 35.5 mg/g, and is cheap, and can effectively separate and recover lithium ions, which is better than adsorption of other metal ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116173915B_ABST
    Figure CN116173915B_ABST
Patent Text Reader

Abstract

A method for preparing an adsorbent modified with fluorine-containing functional groups using cellulose as a carrier relates to a method for preparing an adsorbent using cellulose as a carrier. The present invention aims to solve the technical problems of poor adsorption selectivity, low adsorption capacity and high cost of existing adsorbents for lithium ions. The present invention synthesizes an adsorbent material modified with pentafluoropropionate groups using cellulose as a carrier. The preparation method is simple, the cost is low, and the material has high selectivity and adsorption capacity. The adsorbent material of the present invention can adsorb lithium ions in a monovalent / high-valent metal mixed solution with high adsorption capacity and high selectivity. The adsorption of lithium ions is much better than that of sodium, potassium, nickel, cobalt, manganese and copper ions. The adsorption capacity of lithium ions can reach up to 35.5 mg / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing an adsorbent using cellulose as a carrier. Background Art

[0002] Lithium is called "white oil". Under the global carbon peak and carbon neutrality environment, the new energy industry has developed rapidly, and the market demand for new energy vehicles has exploded, resulting in a sharp increase in the demand for lithium. At present, most of the world's lithium resources come from Australian lithium mines and South American salt lakes. my country's lithium resource development reserves are relatively low, and the degree of external dependence is as high as 70%, which is difficult to meet the needs of my country's rapid industrial and social development. Therefore, clean and efficient recovery of lithium from lithium-containing wastewater is crucial to replenish my country's lithium resources and prevent waste lithium ions from causing secondary pollution to the human body and the environment. However, the composition of lithium-containing wastewater is very complex and contains a large number of anionic and cationic impurities, which makes the extraction process very cumbersome and difficult. Lithium extraction by adsorption is a lithium extraction method with simple process, high recovery efficiency, strong lithium ion selectivity, no pollution to the environment, and relatively low production cost. It has great advantages in terms of economy and environmental protection. The adsorption method is mainly divided into inorganic ion adsorption method and organic ion adsorption method. Inorganic ion adsorbents have high lithium selectivity, mainly including aluminum salt adsorbents, monoclinic antimonic acid and antimonate type, amorphous hydroxide, ion sieve oxide, layered multivalent metal acid salt type, etc. Aluminum salt adsorbents have the advantages of no need for molding and granulation, long life, and low loss, but the adsorption capacity of this adsorbent is relatively low, and the concentration of sodium ions, potassium ions and other ions in lithium-containing wastewater has a greater impact on its selectivity. Monoclinic antimonic acid and antimonate type adsorbents have good stability and low antimony dissolution, but this adsorbent came out relatively late, and there is a lack of extensive research on the application of antimonates. Amorphous hydroxide adsorbents are mostly made of aluminum oxides and hydrous oxides as raw materials. The strength of their adsorption of lithium ions is positively correlated with the concentration of lithium ions in the solution. They can be recycled, and other elements in the solution have little effect on them. They have high selectivity, but this adsorbent is more suitable for lithium extraction from salt lake brine with a high magnesium-aluminum ratio. Ion sieve oxide adsorbents have been widely studied on manganese ion sieves and titanium ion sieves. They have good selectivity, low cost, large adsorption capacity and good stability. However, the powdered form of this adsorbent material leads to poor exchange performance and severe dissolution loss, which is not conducive to column operation and requires granulation. However, it is difficult for granular ion sieves to guarantee the selectivity and adsorption capacity of the original powdered ion sieve. Layered ion exchange adsorbents have strong selectivity for lithium ions, but this adsorbent is toxic and is therefore generally not used in actual production. Organic ion adsorbents generally rely on Coulomb force to adsorb lithium ions through ion exchange resins, but due to the limitations of their physicochemical properties, this adsorbent has low selectivity for lithium ions and has a high cost for large-scale use.

[0003] Cellulose is a natural organic polymer that is biodegradable, widely available, non-toxic, pollution-free, easy to modify, chemically stable, biocompatible, renewable, and cheap. It is widely distributed in nature and has abundant reserves. The basic structural unit of cellulose is glucose, which contains a large number of hydroxyl groups. The hydroxyl groups not only form a large number of hydrogen bonds between and within its molecules, making its structure more stable, but also provide sites for chemical modification, making it easy to modify different functional groups. However, cellulose is difficult to dissolve in water and organic solvents, which greatly restricts the development and use of cellulose functional materials. Therefore, how to design and prepare cellulose-based adsorption materials with stable structure, high adsorption capacity, and high adsorption selectivity has become a hot topic and difficulty in current research. Summary of the invention

[0004] The present invention aims to solve the technical problems of poor adsorption selectivity, low adsorption capacity and high cost of existing adsorbents for lithium ions, and to provide a preparation method of an adsorbent modified with fluorine-containing functional groups using cellulose as a carrier.

[0005] The preparation method of the present invention of the fluorine-containing functional group adsorbent using cellulose as a carrier and then modified is carried out according to the following steps:

[0006] 1. Add ionic liquid into a round-bottom flask, and then place the ionic liquid and cellulose in a vacuum drying oven at 80℃~85℃ for 24h~25h;

[0007] The ionic liquid is 1-allyl-3-methylimidazolium bromide;

[0008] 2. Add the cellulose dried under vacuum in step 1 into the round-bottom flask containing the ionic liquid, seal it with a rubber stopper, connect the rubber stopper to a vacuum pump, put the round-bottom flask into an oil bath at 80°C to 85°C, start the vacuum pump to evacuate the round-bottom flask to a vacuum state, and then stir magnetically for 4h to 5h until the cellulose is completely dissolved;

[0009] The mass ratio of cellulose to ionic liquid is 1:(9-25);

[0010] 3. Disconnect the vacuum pump, take out the medium round-bottom flask in step 2 from the oil bath, inject N,N-dimethylformamide from the top of the rubber stopper with a syringe, and then continue magnetic stirring for 1h to 2h; open the rubber stopper, add iodine, and then quickly connect the dropping funnel, and introduce nitrogen, and stir magnetically until the iodine is completely dissolved, and then immediately add pentafluoropropionic anhydride dropwise with the dropping funnel, and continue magnetic stirring at room temperature for 24h to 25h to obtain a mixed solution;

[0011] The mass ratio of the cellulose to the volume ratio of N,N-dimethylformamide is 1g:(6mL-18mL);

[0012] The mass ratio of the iodine element to the cellulose is 1:(33-100);

[0013] The volume ratio of pentafluoropropionic anhydride to N,N-dimethylformamide is 1:(3-4.5);

[0014] 4. ①, add the mixed solution obtained in step 3 to the magnetically stirred ice-water mixture with a plastic dropper for sedimentation, then stir and wash for 15min to 20min, filter and retain the filter cake;

[0015] The volume ratio of the mixed solution obtained in step 3 to the ice-water mixture is 1:(10-20);

[0016] ②. Add deionized water to the filter cake and clean it with magnetic stirring for 15min to 20min, then filter it and keep the filter cake;

[0017] ③. Repeat step ② until the filtrate is clear and colorless;

[0018] ④. Place the filter cake in methanol and clean it with magnetic stirring for 15min to 20min, then filter and keep the filter cake;

[0019] ⑤. Repeat step ④ twice, add ethanol to rinse the filter cake, filter with suction, retain the filter cake, and obtain the product;

[0020] 5. Place the product obtained in step 4 in a vacuum drying oven, dry at a constant temperature of 45° C. to 55° C. for 10 h to 12 h, and cool to room temperature to obtain an adsorbent material with cellulose as a carrier and modified with pentafluoropropionate groups.

[0021] The present invention is a preparation method of a fluorine-containing functional group adsorbent material modified by using cellulose as a carrier, characterized in that the solvent for dissolving cellulose is 1-allyl-3-methylimidazolium bromide ion liquid, the adsorbent material carrier is cellulose, and the functional monomer used in the product is pentafluoropropionic anhydride.

[0022] The adsorbent material carrier used in the method of the present invention is cellulose. The basic structural unit of cellulose contains a large number of hydroxyl groups, which not only forms a large number of hydrogen bonds between and within its molecules, making its structure more stable, but also provides sites for chemical modification, making it easy to modify different functional groups. Compared with traditional adsorbent materials, cellulose-based adsorbent materials have many advantages such as low price, easy degradation, and environmental friendliness.

[0023] The functional monomer used in the method of the present invention is pentafluoropropionic anhydride. Pentafluoropropionic anhydride contains fluorine element, which can provide more adsorption sites to stably bind to lithium ions. Through theoretical calculations of the combination of fluorine element and monovalent metals, the binding energy of fluorine and lithium is the lowest, and the fluorine-containing functional monomer will preferentially bind to lithium to show selectivity; secondly, the use of anhydride for modification has certain rationality and high feasibility after long-term verification; compared with other fluorine-containing anhydrides (trifluoroacetic anhydride and heptafluorobutyric acid rod), pentafluoropropionic anhydride has the advantages of a more suitable boiling point reaction, easier preparation, and low price, so pentafluoropropionic acid rod is selected as the reaction group.

[0024] The present invention synthesizes an adsorbent material modified with pentafluoropropionate groups using cellulose as a carrier, which has a simple preparation method, low cost, and high selectivity and adsorption capacity. The adsorbent material of the present invention can adsorb lithium ions in a monovalent / high-valent metal mixed solution with high adsorption capacity and high selectivity, and the adsorption of lithium ions is much better than that of sodium, potassium, nickel, cobalt, manganese and copper ions, and the adsorption capacity of lithium ions can reach up to 35.5 mg / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The synthetic molecular formula flow chart of the adsorbent modified with pentafluoropropionate groups after using cellulose as a carrier of the present invention;

[0026] Figure 2 is a SEM image of cellulose in step 1 of experiment 1;

[0027] Figure 3 This is the SEM image of the adsorbent material prepared in Experiment 1 with cellulose as the carrier and then modified with pentafluoropropionate groups;

[0028] Figure 4 Mapping diagram of the adsorbent material prepared in Experiment 1 with cellulose as carrier and then modified with pentafluoropropionate groups;

[0029] Figure 5 is the infrared spectrum;

[0030] Figure 6 is the isothermal adsorption curve;

[0031] Figure 7 The selective adsorption capacity of the adsorbent material modified with pentafluoropropionate groups on cellulose as a carrier for lithium ions in a monovalent mixed solution;

[0032] Figure 8 The selective adsorption capacity of the adsorbent material with cellulose as a carrier and modified with pentafluoropropionate groups for lithium ions in a high-valent mixed solution. DETAILED DESCRIPTION

[0033] Specific implementation method 1: This implementation method is a method for preparing a fluorine-containing functional group adsorbent using cellulose as a carrier and then modified, which is specifically carried out according to the following steps:

[0034] 1. Add ionic liquid into a round-bottom flask, and then place the ionic liquid and cellulose in a vacuum drying oven at 80℃~85℃ for 24h~25h;

[0035] The ionic liquid is 1-allyl-3-methylimidazolium bromide;

[0036] 2. Add the cellulose dried under vacuum in step 1 into the round-bottom flask containing the ionic liquid, seal it with a rubber stopper, connect the rubber stopper to a vacuum pump, put the round-bottom flask into an oil bath at 80°C to 85°C, start the vacuum pump to evacuate the round-bottom flask to a vacuum state, and then stir magnetically for 4h to 5h until the cellulose is completely dissolved;

[0037] The mass ratio of cellulose to ionic liquid is 1:(9-25);

[0038] 3. Disconnect the vacuum pump, take out the medium round-bottom flask in step 2 from the oil bath, inject N,N-dimethylformamide from the top of the rubber stopper with a syringe, and then continue magnetic stirring for 1h to 2h; open the rubber stopper, add iodine, and then quickly connect the dropping funnel, and introduce nitrogen, and stir magnetically until the iodine is completely dissolved, and then immediately add pentafluoropropionic anhydride dropwise with the dropping funnel, and continue magnetic stirring at room temperature for 24h to 25h to obtain a mixed solution;

[0039] The mass ratio of the cellulose to the volume ratio of N,N-dimethylformamide is 1g:(6mL-18mL);

[0040] The mass ratio of the iodine element to the cellulose is 1:(33-100);

[0041] The volume ratio of pentafluoropropionic anhydride to N,N-dimethylformamide is 1:(3-4.5);

[0042] 4. ①, add the mixed solution obtained in step 3 to the magnetically stirred ice-water mixture with a plastic dropper for sedimentation, then stir and wash for 15min to 20min, filter and retain the filter cake;

[0043] The volume ratio of the mixed solution obtained in step 3 to the ice-water mixture is 1:(10-20);

[0044] ②. Add deionized water to the filter cake and clean it with magnetic stirring for 15min to 20min, then filter it and keep the filter cake;

[0045] ③. Repeat step ② until the filtrate is clear and colorless;

[0046] ④. Place the filter cake in methanol and clean it with magnetic stirring for 15min to 20min, then filter and keep the filter cake;

[0047] ⑤. Repeat step ④ twice, add ethanol to rinse the filter cake, filter with suction, retain the filter cake, and obtain the product;

[0048] 5. Place the product obtained in step 4 in a vacuum drying oven, dry at a constant temperature of 45° C. to 55° C. for 10 h to 12 h, and cool to room temperature to obtain an adsorbent material with cellulose as a carrier and modified with pentafluoropropionate groups.

[0049] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that in step 1, an ionic liquid is added to a round-bottom flask, and then the ionic liquid and cellulose are placed in a vacuum drying oven at 80° C. and vacuum dried for 24 hours. The rest is the same as specific embodiment 1.

[0050] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: in step two, the cellulose vacuum-dried in step one is added to a round-bottom flask containing an ionic liquid, sealed with a rubber stopper, the rubber stopper is connected to a vacuum pump, the round-bottom flask is placed in an 80°C oil bath, the vacuum pump is started to evacuate the round-bottom flask to a vacuum state, and then magnetically stirred for 4 hours until the cellulose is completely dissolved. The rest is the same as specific implementation method one or two.

[0051] Specific embodiment 4: This embodiment differs from Specific embodiments 1 to 3 in that: in step 3, the vacuum pump is disconnected, the round-bottom flask in step 2 is taken out of the oil bath, N,N-dimethylformamide is injected from the top of the rubber stopper with a syringe, and then magnetic stirring is continued for 1 hour. The rest is the same as Specific embodiments 1 to 3.

[0052] Specific embodiment 5: This embodiment is different from specific embodiment 4 in that in step 5, the product obtained in step 4 is placed in a vacuum drying oven, dried at 45°C for 12 hours, and cooled to room temperature to obtain an adsorbent material with cellulose as a carrier and modified with pentafluoropropionate groups. The rest is the same as specific embodiment 4.

[0053] The present invention is verified by the following tests:

[0054] Experiment 1: This experiment is a preparation method of a fluorine-containing functional group adsorbent modified with cellulose as a carrier, which is specifically carried out in the following steps:

[0055] 1. Add 45 g of ionic liquid into a round-bottom flask, and then place 45 g of ionic liquid and 2 g of cellulose in a vacuum drying oven at 80 °C for 24 h;

[0056] The ionic liquid is 1-allyl-3-methylimidazolium bromide;

[0057] 2. Add the cellulose dried under vacuum in step 1 into the round-bottom flask containing the ionic liquid, seal it with a rubber stopper, connect the rubber stopper to a vacuum pump, put the round-bottom flask into an 80°C oil bath, start the vacuum pump to evacuate the round-bottom flask to a vacuum state, and then stir it magnetically for 5 hours until the cellulose is completely dissolved;

[0058] 3. Disconnect the vacuum pump, take out the medium round-bottom flask in step 2 from the oil bath, inject 32 mL of N,N-dimethylformamide from the top of the rubber stopper with a syringe, and then continue magnetic stirring for 1 hour; open the rubber stopper, add 52 mg of iodine, and then quickly connect the dropping funnel, and pass nitrogen, and stir magnetically until the iodine is completely dissolved, and then immediately add 10 mL of pentafluoropropionic anhydride with the dropping funnel, and continue magnetic stirring at room temperature for 24 hours to obtain a mixed solution;

[0059] 4. ①, add the mixed solution obtained in step 3 to the magnetically stirred ice-water mixture with a plastic dropper for sedimentation, then stir and wash for 15 minutes, filter and retain the filter cake;

[0060] The volume ratio of the mixed solution obtained in step 3 to the ice-water mixture is 1:10;

[0061] ②. Add deionized water to the filter cake and wash it with magnetic stirring for 15 minutes, then filter it and keep the filter cake;

[0062] ③. Repeat step ② until the filtrate is clear and colorless;

[0063] ④. Place the filter cake in methanol and stir it under magnetic stirring for 15 minutes, filter it and keep the filter cake;

[0064] ⑤. Repeat step ④ twice, add ethanol to rinse the filter cake, filter with suction, retain the filter cake, and obtain the product;

[0065] The volume of methanol used at a time is 200 mL;

[0066] The volume ratio of the ethanol used once to the filter cake is 10:1;

[0067] 5. The product obtained in step 4 is placed in a vacuum drying oven, dried at a constant temperature of 45° C. for 10 h, and cooled to room temperature to obtain an adsorbent material with cellulose as a carrier and modified with pentafluoropropionate groups.

[0068] Figure 2 This is the SEM image of cellulose in step 1 of experiment 1. Figure 3This is the SEM image of the adsorbent material prepared in Experiment 1, which was modified with pentafluoropropionate groups after using cellulose as a carrier. It can be seen that the cellulose before modification has a filamentous material with a smooth and flat surface, while the surface of the material after modification with pentafluoropropionate is relatively rough, producing many irregular pores. This indicates that the adsorbent material modified with pentafluoropropionate groups after using cellulose as a carrier was successfully prepared.

[0069] Figure 4 This is the mapping diagram of the adsorbent material prepared in Experiment 1, which was modified with pentafluoropropionate groups after using cellulose as a carrier. It shows the element distribution of carbon, oxygen and fluorine. It can be seen that the fluorine element is evenly distributed and abundant after modification, proving that the pentafluoropropionate groups were successfully modified onto the cellulose and the adsorbent material was successfully prepared.

[0070] Fourier transform infrared spectroscopy was performed on the adsorbent material prepared in Experiment 1 with cellulose as the carrier and then modified with pentafluoropropionate groups before and after modification. Figure 5 is an infrared spectrum, wherein curve A is the cellulose in step 1 of experiment 1, and curve B is the adsorbent material prepared in experiment 1 with cellulose as a carrier and then modified with pentafluoropropionate groups. From curve B, it can be seen that the prepared adsorbent material has a peak at 1792 cm -1 The characteristic peak of C=O appears at 1140cm -1 The characteristic peak of CF appears at , while the other characteristic peaks are basically the same. This shows that the adsorbent material prepared in Experiment 1 successfully modified the pentafluoropropionate group onto cellulose, and the adsorbent material modified with pentafluoropropionate group after using cellulose as a carrier was successfully prepared.

[0071] The adsorbent material prepared in Experiment 1 with cellulose as the carrier and then modified with pentafluoropropionate groups was used to conduct adsorption experiments on lithium ion aqueous solutions of different concentrations. The test method is as follows:

[0072] (1) preparing lithium nitrate aqueous solutions with lithium concentrations of 20 mg / L, 60 mg / L, 80 mg / L, 100 mg / L, 150 mg / L, 200 mg / L, 300 mg / L, 500 mg / L, 600 mg / L and 700 mg / L, respectively; taking 20 mL of each of the lithium-containing solutions with different concentrations and placing them in 10 conical flasks with a specification of 50 mL each;

[0073] (2) Weigh 20 mg of the adsorbent material prepared in Experiment 1 and modified with pentafluoropropionate groups using cellulose as a carrier, and weigh 10 portions in total. Put them into 50 mL conical flasks containing lithium ion aqueous solutions of different concentrations, and set the parameters as follows: temperature 25 °C, rotation speed 180 rpm, and time 24 h in a constant temperature oscillator for adsorption experiment;

[0074] (3) taking the solution before and after adsorption in the conical flask respectively, and measuring the lithium ion concentration in the solution using an atomic absorption spectrometer (AAS);

[0075] Figure 6 This is the isothermal adsorption curve diagram. The fitting shows that the maximum adsorption capacity Qmax of the adsorbent material modified with pentafluoropropionate groups after using cellulose as a carrier for lithium ions is 35.5 mg / g.

[0076] The adsorbent material prepared in Experiment 1 and modified with pentafluoropropionate groups using cellulose as a carrier was used to analyze the adsorption selectivity of lithium ions in a monovalent mixed solution. The test method is as follows:

[0077] (1) Prepare a mixed aqueous solution containing 5 mmol / L lithium ions, 5 mmol / L sodium ions, and 5 mmol / L potassium ions, with a volume of 20 mL, weigh three portions for parallel testing, and place them in 50 mL conical flasks respectively;

[0078] (2) Weigh 20 mg of the adsorbent material prepared in Experiment 1 and modified with pentafluoropropionate groups using cellulose as a carrier, and put it into the mixed aqueous solution. The parameters were set as follows: temperature 25°C, rotation speed 180 rpm, and time 24 h in a constant temperature oscillator for adsorption experiment;

[0079] (3) taking the ion solutions before and after adsorption in the conical flask respectively, and determining the concentrations of lithium ions, sodium ions, and potassium ions in the solutions using inductively coupled plasma mass spectrometry (ICP MS); Figure 7 The selective adsorption capacity of the adsorbent material modified with pentafluoropropionate groups on cellulose as a carrier for lithium ions in a monovalent metal mixed solution shows that the adsorbent material modified with pentafluoropropionate groups on cellulose as a carrier can separate lithium ions from a mixed solution containing sodium ions and potassium ions, indicating that the adsorbent material can also separate and recover lithium ions in a monovalent metal mixed solution containing sodium ions, potassium ions, etc., which have a greater influence on the adsorption selectivity.

[0080] The adsorbent material prepared in Experiment 1 and modified with pentafluoropropionate groups using cellulose as a carrier was used to analyze the adsorption selectivity of lithium ions in a high-valent mixed solution. The test method is as follows:

[0081] (1) A mixed aqueous solution containing 5 mmol / L lithium ions, 5 mmol / L nickel ions, 5 mmol / L cobalt ions, 5 mmol / L manganese ions and 5 mmol / L copper ions was prepared with a volume of 20 mL, and three portions were weighed for parallel testing; each portion was placed in a 50 mL conical flask;

[0082] (2) Weigh 20 mg of the adsorbent material prepared in Experiment 1 and modified with pentafluoropropionate groups using cellulose as a carrier, and put it into the mixed aqueous solution. The parameters were set as follows: temperature 25°C, rotation speed 180 rpm, and time 24 h in a constant temperature oscillator for adsorption experiment;

[0083] (3) taking the ion solutions before and after adsorption in the conical flask respectively, and determining the concentrations of lithium ions, nickel ions, cobalt ions, manganese ions and copper ions in the solutions using inductively coupled plasma mass spectrometry (ICP MS); Figure 8 The selective adsorption capacity of the adsorbent material modified with pentafluoropropionate groups on cellulose as a carrier for lithium ions in a mixed solution of high-valent metals shows that the adsorbent material modified with pentafluoropropionate groups on cellulose as a carrier can highly selectively separate lithium ions from a mixed solution containing nickel ions, cobalt ions, manganese ions and copper ions, indicating that the adsorbent material can separate and recover lithium ions in a high-valent mixed solution containing nickel ions, cobalt ions and the like.

Claims

1. A method for preparing a fluorine-containing functional group adsorbent using cellulose as a carrier, characterized in that The preparation method of the fluorine-containing functional group adsorbent modified with cellulose as a carrier is carried out according to the following steps:

1. Add ionic liquid into a round-bottom flask, and then place the ionic liquid and cellulose in a vacuum drying oven at 80℃~85℃ for 24h~25h; The ionic liquid is 1-allyl-3-methylimidazolium bromide; 2. Add the cellulose dried under vacuum in step 1 into the round-bottom flask containing the ionic liquid, seal it with a rubber stopper, connect the rubber stopper to a vacuum pump, put the round-bottom flask into an oil bath at 80°C to 85°C, start the vacuum pump to evacuate the round-bottom flask to a vacuum state, and then stir magnetically for 4h to 5h until the cellulose is completely dissolved; The mass ratio of cellulose to ionic liquid is 1:(9-25); 3. Disconnect the vacuum pump, take out the medium round-bottom flask in step 2 from the oil bath, inject N,N-dimethylformamide from the top of the rubber stopper with a syringe, and then continue magnetic stirring for 1h to 2h; open the rubber stopper, add iodine, and then quickly connect the dropping funnel, and introduce nitrogen, and stir magnetically until the iodine is completely dissolved, and then immediately add pentafluoropropionic anhydride dropwise with the dropping funnel, and continue magnetic stirring at room temperature for 24h to 25h to obtain a mixed solution; The mass ratio of the cellulose to the volume ratio of N,N-dimethylformamide is 1g:(6mL-18mL); The mass ratio of the iodine element to the cellulose is 1:(33-100); The volume ratio of pentafluoropropionic anhydride to N,N-dimethylformamide is 1:(3-4.5); 4. ①, add the mixed solution obtained in step 3 to the magnetically stirred ice-water mixture with a plastic dropper for sedimentation, then stir and wash for 15min to 20min, filter and retain the filter cake; The volume ratio of the mixed solution obtained in step 3 to the ice-water mixture is 1:(10-20); ②. Add deionized water to the filter cake and clean it with magnetic stirring for 15min to 20min, then filter it and keep the filter cake; ③. Repeat step ② until the filtrate is clear and colorless; ④. Place the filter cake in methanol and clean it with magnetic stirring for 15min to 20min, then filter and keep the filter cake; ⑤. Repeat step ④ twice, add ethanol to rinse the filter cake, filter with suction, retain the filter cake, and obtain the product; 5. Place the product obtained in step 4 in a vacuum drying oven, dry at a constant temperature of 45° C. to 55° C. for 10 h to 12 h, and cool to room temperature to obtain an adsorbent material with cellulose as a carrier and modified with pentafluoropropionate groups.

2. The method for preparing a fluorine-containing functional group adsorbent using cellulose as a carrier and post-modified according to claim 1, characterized in that In step 1, the ionic liquid is added into the round-bottom flask, and then the ionic liquid and cellulose are placed in a vacuum drying oven at 80° C. for 24 hours under vacuum.

3. The method for preparing a fluorine-containing functional group adsorbent using cellulose as a carrier and post-modified according to claim 1, characterized in that In step 2, the cellulose vacuum-dried in step 1 is added to a round-bottom flask containing ionic liquid, sealed with a rubber stopper, the rubber stopper is connected to a vacuum pump, the round-bottom flask is placed in an 80°C oil bath, the vacuum pump is started to evacuate the round-bottom flask to a vacuum state, and then magnetically stirred for 4 hours until the cellulose is completely dissolved.

4. The method for preparing a fluorine-containing functional group adsorbent using cellulose as a carrier and post-modified according to claim 1, characterized in that In step 3, disconnect the vacuum pump, take out the medium round-bottom flask in step 2 from the oil bath, inject N,N-dimethylformamide from the top of the rubber stopper with a syringe, and then continue magnetic stirring for 1 hour.

5. The method for preparing a fluorine-containing functional group adsorbent using cellulose as a carrier and post-modified according to claim 1, characterized in that In step 5, the product obtained in step 4 is placed in a vacuum drying oven, dried at a constant temperature of 45° C. for 12 hours, and cooled to room temperature to obtain an adsorbent material with cellulose as a carrier and modified with pentafluoropropionate groups.

Citation Information

Patent Citations

  • Fluorine-contained hydrophobic oil-proof modified nanocellulose for food packaging paper and preparation method of nanocellulose

    CN110804105A

  • Method for selectively extracting lithium from lithium-containing wastewater by using fluorine-containing polymer adsorbent

    CN114134342A